Peta Pertumbuhan Ekonomi Pada Negara ASEAN-6 (2012-2020) Perspektif Ekonomi Syariah - Abdi Asmo; Rozalinda; Ahmad Wira (Al-Musthofa: Journal of Sharia Economics, 2023)
This study aims to map how economic growth has occurred in ASEAN-6 countries during 2012-2020 and how economic growth has been from an Islamic economic perspective. In answering this, the researcher used a mixed-method research design with secondary data sources and literature reviews. Based on the results of the study, it can be concluded that the economic growth map of ASEA countries, seen from the highest Gross Domestic Product (GDP), namely Indonesia ranks first, followed by Thailand, the Philippines, Singapore, Malaysia and Vietnam. Data on the development of economic growth shows that Thailand was the country with the highest economic growth in 2012 followed by the Philippines, Vietnam, Indonesia, Malaysia and Singapore. Islamic economics has a view of economic growth that does not only pay attention to production factors but economic equity. Agreements in the economic field carried out by ASEAN countries gave birth to an agreement called the "ASEAN Economic Community Blueprint (AEC)". Through this, ASEAN countries have shown concern for the equality of the people's economy with the principle of economic growth based on Islamic economics.